2022
DOI: 10.3389/fnut.2022.807071
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Processing Technology of Cornus officinalis: Based on Anti-Fibrotic Activity

Abstract: Graphical AbstractThe processing technology of C. officinalis was optimized in terms of its anti-fibrotic activity. Differences in its chemical composition after the preparation were detected by UHPLC-Q-TOF-MS/MS. These results provide material basis for further exploring the role of C. officinalis in liver and kidney protection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Cornus officinalis was obtained from Pan'an City of Zhejiang Province and authenticated by Prof. Bo Zhu and Kaohua Liu. The preparations of cornus officinalis with or without HPWS according to the experimental conditions as described earlier [ 19 ]. In brief, a certain amount of cornus officinalis samples was braised with rice wine dosage ( m / m ) at 25% for 1 h, following steamed at 115 °C for 1 h, and dried at 60 °C, finally the cornus officinalis with HPWS were obtained.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cornus officinalis was obtained from Pan'an City of Zhejiang Province and authenticated by Prof. Bo Zhu and Kaohua Liu. The preparations of cornus officinalis with or without HPWS according to the experimental conditions as described earlier [ 19 ]. In brief, a certain amount of cornus officinalis samples was braised with rice wine dosage ( m / m ) at 25% for 1 h, following steamed at 115 °C for 1 h, and dried at 60 °C, finally the cornus officinalis with HPWS were obtained.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that early liver fibrosis can be reversed once the injury ceases, with approximately half of activated HSCs returning to an inactive state via apoptosis or deactivation [ 18 ]. Our previous study showed that cornus officinalis could inhibit the activation of HSCs, and its high pressure wine steaming (HPWS) products has a superior inhibitory effect [ 19 ]. Consistently, it is reported that the regulatory effects on the pharmacology of cornus officinalis differ between the were raw and post-processed [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several studies have been carried out to analyze the changes in components between raw CF and wine-processed CF ( Cao et al, 2020 ; Han et al, 2022 ). Previous studies revealed that several iridoids showed significant differences in raw CF and wine-processed CF by HPLC-MS ( Wang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%